2013
DOI: 10.1002/bbb.1429
|View full text |Cite
|
Sign up to set email alerts
|

Managing a second‐generation crop portfolio through sustainable intensification: Examples from the USA and the EU

Abstract: Sustainable intensification of agricultural systems has been suggested – in addition to reducing waste and changing consumption habits – as a way to increase food, feed, fuel, and fiber security in the twenty‐first century. Here we describe three primary strategies of agricultural intensification – conventional intensification, temporal intensification, and spatial intensification – and how they can be used to manage and integrate food and second‐generation crop portfolios. While each strategy has individual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 53 publications
1
80
0
Order By: Relevance
“…Examples are an inclusion of switchgrass or mixed-grass-forb prairie in maize production [24], strips of wildflower mixtures for biogas in maize-dominated areas [70] and alternative crops to maize, such as the cup plant Silphium perfoliatum L. [71]. Including dedicated energy crops, perennial crops in particular, in intensive foodcropping systems could mitigate some of the pressures on farmland biodiversity by lowering input levels, lowering the speed of production cycles, increasing crop diversity, regenerating soils and providing continuous resources for ecosystem service providers [24,50,72,73].…”
Section: A2: Combination Of First-generation and Dedicated Energy Cromentioning
confidence: 99%
See 2 more Smart Citations
“…Examples are an inclusion of switchgrass or mixed-grass-forb prairie in maize production [24], strips of wildflower mixtures for biogas in maize-dominated areas [70] and alternative crops to maize, such as the cup plant Silphium perfoliatum L. [71]. Including dedicated energy crops, perennial crops in particular, in intensive foodcropping systems could mitigate some of the pressures on farmland biodiversity by lowering input levels, lowering the speed of production cycles, increasing crop diversity, regenerating soils and providing continuous resources for ecosystem service providers [24,50,72,73].…”
Section: A2: Combination Of First-generation and Dedicated Energy Cromentioning
confidence: 99%
“…Trials have found CFE to be considerably less resource demanding and more amenable to sustainable production than conventional food-cropping systems [49]. In the developed countries, CFE systems are also expected to improve overall ecosystem functions [50]. Land sharing of food and energy crops could thus be a means of supporting sustainable intensification of agriculture [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional options for diversifying landscapes and cropping systems include the use of mixed species pastures for dairy and beef production (Sulc and Tracy, 2007); perennial grains for food and feed production (Cox et al, 2006); cover crops to fill otherwise unoccupied temporal niches (Snapp et al, 2005); dedicated perennial grasses and native mixed-species communities for biofuel feedstock production (Heaton et al, 2013); herbaceous and woody species for reconstructing wetlands (Zedler, 2003) and riparian corridors (Schultz et al, 2004); and trees for agroforestry plantations ( Jose et al, 2012).…”
mentioning
confidence: 99%
“…Thus, in addition to the need to supply farmers with necessary technical information and inputs for producing non-traditional crops, planning for generating a critical mass of producers and the development of expedited paths to markets are needed. This is particularly true in the case of 'second-generation' bioenergy crops, for which new biomass collection strategies and processing facilities are needed (Heaton et al, 2013).…”
mentioning
confidence: 99%